The Possibilty of Using Dual and Plural Forms on Arabic Verbal Noun: Critical Analysis of al-Maqasid as-Syafiyyah by Imam Syatibi - Zainal Abidin Hajib; Hishomuddin Ahmad; Maskanatul Fiqiyah (University of Darussalam Gontor, 2018)
The present knowledge of Arabic grammar was not structurally studied in Jahiliyyah period and early Islamic periods by companions of Prophet Muhammad PBUH. The Arab spoke their language fluently without any linguistic barriers in their tongue. The Arabic grammar was introduced after Islam was spread among non-Arab in neighboring countries. Muslim scholars began to protect Arabic language principles from misused by non-Arab speakers through compiling Arabic grammar from Arabian tribes and Bedouins in Middle of Arabian Peninsula, the original homeland of the Arab people. Among the prominent Arabic grammarian scholars in 8th century of Hijrah was al-Syatibi. While writing his great Arabic grammar book, al-Maqasid as-Syafiyyah li Sarhi Alfiyyah Ibn Malik, he criticized another scholars arguments and formed his own opinions. In addition al-Syatibi also did not follow any school of thoughts without any arguments or proofs. This paper aims to analyzed the al-Syatibi’s opinion on the possibility of using dual or plural form on verbal noun or gerund. Analytical method was employed by comparing grammarians’ opinions from various type of books. The convincing arguments were used in the judgement by using strong opinions. The result showed al-Syatibi agreed on the possibility of using dual or plural form on verbal noun. It was supported by az-Zajjaji and Ibn Malik’s opinions in their books.ملخص لم يكن علم النحو معروفا في العصر الجاهلي ولا في أوائل عصر الصحابة رضي الله عنهم، وما ذاك إلا لعدم الحاجة إليه؛ لأنهم كانوا يتكلمون العربية الفصحى بطلاقة، وعندما انتشرت الفتوح الإسلامية ودخل كثير من الأعاجم في الإسلام واختلطوا مع المسلمين العرب برزت الحاجة لهذا العلم. ومن كبار العلماء في القرن الثامن من الهجرية هو الإمام الشاطبي رحمه الله الذي ألّف كتاب المقاصد الشافية شرح الألفية ابن مالك. لقد امتاز في شرحه باستقلال الرأي، وحرّيّة الفكر، فلا يقلّد غيره، ولايذهب إلى مذهب دون حجة أو برهان. وتهدف هذه الدراسة إلى تجلية النظرة النقدية عن حكم تثنية المصدر المبين للنوع وجمعه عند الإمام الشّاطبي رحمه الله. وتسلك الدراسة المنهج التحليلي، وذلك بمقارنة آراء العلماء حول المصدر من كتب النحو والصرف واللغة والبلاغة، وترجيح القوى من الضعيف. وأبرزت النتيجة أنّ تثنية المصدر المبين للنوع وجمعه جائز وهو مذهب الزجاجي وابن مالك.الكلمات المفتاحية: المصدر، تثنية، جمع، الإمام الشّاطبي رحمه الله.